Pattern Recognition Receptors in Multiple Sclerosis and Its Animal Models - Deerhake, M. Elizabeth; Biswas, Debolina D.; Barclay, William E.; Shinohara, Mari L. (Frontiers in Immunology, 2019)
Pattern recognition receptors (PRRs) coordinate the innate immune response and have a significant role in the development of multiple sclerosis (MS). Accumulating evidence has identified both pathogenic and protective functions of PRR signaling in MS and its animal model, experimental autoimmune encephalomyelitis (EAE). Additionally, evidence for PRR signaling in non-immune cells and PRR response to host-derived endogenous ligands has also revealed new pathways controlling the development of CNS autoimmunity. Many PRRs remain uncharacterized in MS and EAE, and understanding the distinct triggers and functions of PRR signaling in CNS autoimmunity requires further investigation. In this brief review, we discuss the diverse pathogenic and protective functions of PRRs in MS and EAE, and highlight major avenues for future research.